2020
DOI: 10.2174/1381612826666200113162641
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxicity as a Target Against Neurodegenerative Processes

Abstract: : The global burden of neurodegenerative diseases is alarmingly increasing in parallel to the aging of population. Although the molecular mechanisms leading to neurodegeneration are not completely understood, excitotoxicity, defined as the injury and death of neurons due to excessive or prolonged exposure to excitatory amino acids, has been shown to play a pivotal role. The increased release and/or decreased uptake of glutamate results in dysregulation of neuronal calcium homeostasis, leading to oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 187 publications
1
51
0
2
Order By: Relevance
“…The excessive release of glutamate triggers neuronal injury, i.e., excitatory cell death, and this mechanism has been implicated as a main component in the pathogenesis underlying ischemic neuronal cell death, as well as neurodegenerative diseases such as ALS [ 58 , 59 ]. In addition to glutamate toxicity, the hyperexcitation of motor neurons per se induces oxidative stress leading to mitochondrial dysfunction and eventual cell death [ 58 , 59 ]. To prevent glutamate-induced excitotoxicity, glutamate must be taken up by astroglial endfeet that envelope the synapse immediately after its release into the synaptic cleft.…”
Section: Glutamate Released From Neurons Triggers Increased Ppp Flux In Astrogliamentioning
confidence: 99%
See 2 more Smart Citations
“…The excessive release of glutamate triggers neuronal injury, i.e., excitatory cell death, and this mechanism has been implicated as a main component in the pathogenesis underlying ischemic neuronal cell death, as well as neurodegenerative diseases such as ALS [ 58 , 59 ]. In addition to glutamate toxicity, the hyperexcitation of motor neurons per se induces oxidative stress leading to mitochondrial dysfunction and eventual cell death [ 58 , 59 ]. To prevent glutamate-induced excitotoxicity, glutamate must be taken up by astroglial endfeet that envelope the synapse immediately after its release into the synaptic cleft.…”
Section: Glutamate Released From Neurons Triggers Increased Ppp Flux In Astrogliamentioning
confidence: 99%
“…The degeneration of dopaminergic neurons in the substantia nigra and the resultant deficiency in dopamine release in striata causes Parkinson’s disease. The precise mechanism by which dopaminergic neurons degenerate, especially in idiopathic Parkinson’s disease without any apparent mutation in mitochondrial metabolism, remains to be solved [ 44 , 59 , 62 ]. One of the hypothetical mechanisms is oxidative stress induced by the continuous activity of dopaminergic neurons.…”
Section: Activation Of Pentose-phosphate Pathway With Dopamine Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The actin dynamics in neurons regulate extension and direction of axon growth, whereas in the dendritic spines, it (Matsuo et al, 1994;Castellani, 2020) Yes (Terry et al, 1991;Kril et al, 2002;Selkoe, 2002;Coleman et al, 2004) Yes (Swerdlow, 2018;Wang et al, 2020b) Yes (Hynd et al, 2004;Binvignat and Olloquequi, 2020) Yes (Oddo, 2008;Gong et al, 2016) Yes (Fernandez-Perez et al, 2020;George et al, 2020) Yes (DeKosky and Games et al, 1995;Mucke et al, 2000;Scheff and Price, 2003;Coleman et al, 2004;Bjorklund et al, 2012) Parkinson's disease Alpha synuclein Lewy body (Spillantini et al, 1997) Yes (Janezic et al, 2013) Yes (Reinhardt et al, 2013;Pickrell and Youle, 2015) Yes…”
Section: Involvement Of Neuronal Cytoskeleton In C9orf72 Plasticitymentioning
confidence: 99%
“…It has already been shown that glutamate excitotoxicity is implicated in the pathogenesis of TBI [133] and AD [134]. However, the existence of the causal relationship between excitotoxicity and brain insulin resistance indicates that list of disorders associated with brain insulin resistance is much broader and may include stroke [135], PD [136], HD, amyotrophic lateral sclerosis [137], depression, autism spectrum disorder, schizophrenia [138], and multiple sclerosis [139], for which glutamate excitotoxicity has already been demonstrated as a pathogenic factor.…”
Section: Glutamate Excitotoxicity Impairs Activation Of the Neuronal mentioning
confidence: 99%